Xanthohumol-Enriched Beer Does Not Exert Antitumorigenic Effects on HeLa Cell Line In Vivo - Anna Júlia Éliás; Lajos Balogh; Tomáš Brányik; Erzsébet Mák; Éva Csajbókné Csobod; Márta Veresné Bálint; Csilla Benedek (Molecules, 2023)
Xanthohumol is a hop-derived flavonoid that has been widely examined for its health-protecting and antitumorigenic properties, but not yet in a natural beer matrix. The aim of the study was to investigate the antitumorigenic potential of a xanthohumol-enriched beer in vivo. Four groups of 4 × 10 nude mice were formed. Following the injection of HeLa tumorigenic cell lines, the treatment groups were administered a xanthohumol supplementation for 100 days, either dissolved in beer or in an ethanolic solution with the same alcohol strength as beer. The control groups received un-supplemented material. The terminal tumor masses, liver weights, and plasma antioxidant capacities (FRAP and ABTS methods) were measured. For the statistical analysis, a two-way ANOVA test was performed (p < 0.05). There were no statistically significant differences in tumor size between the groups. Xanthohumol did not induce higher levels of plasma antioxidant capacity, neither in beer nor in the water–ethanol matrix. The terminal liver weights were significantly higher in the control group receiving the unsupplemented ethanol solution. Xanthohumol dissolved in beer or in the water–alcohol matrix did not have a protective effect on tumor growth, nor did it have a positive effect on plasma antioxidant capacity either. However, beer with added xanthohumol had a less harmful effect on the liver compared to the supplemented water–ethanol solution. Our results indicate the possible negative countereffect of ethanol; however, further investigations are needed.